Method development and validation using UV spectrophotometry for Nigella sativa oil microparticles quantification - Harun Ismail, Ahmad Fahmi; Doolaanea, Abd Almonem; Mohamed, Farahidah; Mansor, Nur 'Izzati; Mohd Shafri, Mohd Affendi; Yusof, Fathin Athirah (Open Science Publishers LLP Inc., 2015)
Nigella sativa oil (NSO) has been exploited for medical purposes for many generations. The fabrication of microparticles containing NSO intended for sustained release was done to be used in treating osteomyelitis. Method in quantifying NSO using UV-spectroscopy was developed and validated. Linearity shown a good correlation coefficient with the values higher than 0.995, both for actual and different analysts. The LOD and LOQ values were recorded to be 2.89 μg/mL and 8.75 μg/mL respectively. In addition, the highest %RSD values for the intermediate and repeatability studies were 0.970% and 0.445% which suggested the method was precise. The percentage recovery for 4 known concentrations gave the range between 98.16% to 99.39%, indicating the high accuracy of the method. The parameters analyzed in this study were in accordance with ICH Q2 (R1) guidelines.